Exploring Allegorical Schema Modes and Their Impact on Therapists' Chronic Mood Disorders: A Mixed-Method Study - Faghanpour ganji, Mohammad; Kalantari, Mehrdad; Abedi, Ahmad (KMAN Counseling & Psychology Nexus, 2024)
This study aims to examine allegorical schema modes and their influence on therapists' chronic mood disorders. Employing an exploratory mixed-method approach, the research was conducted in two phases. In the initial phase, the dimensions of allegorical schema modes were identified using a two-round Delphi method. In the second phase, the impact of these identified dimensions on therapists’ chronic mood disorders was investigated through an experimental study. Data collection utilized the Brunel Mood Scale, and data analysis was conducted using multivariate analysis of covariance (MANCOVA). The findings indicate that allegorical schema modes significantly affect chronic mood disorders. Specifically, the dimensions of tension, depression, and vigor were influenced by allegorical schema modes, supporting their inclusion. However, no significant effects of allegorical schema modes were observed on the dimensions of anger, confusion, and fatigue, leading to their exclusion. These findings highlight the selective impact of allegorical schema modes on chronic mood disorders in therapists.